Model Pembelajaran Kooperatif dalam Mengatasi Belajar Siswa Hyperaktif dan Slow Learning: Studi Kasus Pada Pelajaran PAI di SDN 2 Padang Kecamatan Singonjuruh - Oktaviani, Yuliana Eka; Habibah, Nur Faiz; Kulzum, Putri Maja Mulia (Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
This study departs from the problem of students who experience learning problems at SDN 2 Padang, Singonjuruh District. Students with the category of hyperactive and slow learning students as problems that must be handled through effective learning models. The cooperative learning model as the basis for the learning approach method chosen to overcome hyperactive and slow learning students, the cooperative learning model applied as an effort to overcome student learning at SDN 2 Padang, Singonjuruh District is the cooperative learning model. The cooperative learning model is a group learning model consisting of 4-6 students heterogeneously. The purpose of the study was to determine how the cooperative learning model overcomes hyperactive and slow learning students. This research is a research based on qualitative field conditions. The approach used in this study uses a case study approach that focuses on phenomena that occur in the field. The data collection method used is through observation data collection, interviews and documentation. In addition, technical triangulation is carried out to validate the data. The results of the research conducted by researchers at SDN 2 Padang can be concluded that: 1) The cooperative learning model is very effective to be applied to hyperactive students because it can help students to complete tasks well and there are changes in behavior in the classroom. Students who experience learning problems of hyperactive students are included in the category of hyperactive impulsive. The cooperative learning model that is effective to be applied to hyperactive impulsive students is the mind mapping type cooperative model. 2) The cooperative learning model is very effective to be applied to slow learning students because it can help students to complete tasks well and make it easier for students to understand the lesson material well. Students who experience learning problems of slow learning students are divided into two categories, namely quiet slow learning and low value slow learning. Both quiet slow learning and low value slow learning, the effective type of cooperative model to be applied is the mind mapping type cooperative model.